Factors Influencing Body Image Perception of University Students in Ghana - Tenkorang, Sylvester; Okyere, Cosmos Osei (Technium Social Sciences Journal, 2022)
This study aimed to find out the perception of University of Cape Cost students about their body image and the factors which influenced their body image perception. Cross-sectional descriptive survey design was adopted for the study. A sample of 380 students was used for the study through the proportional stratified random sampling technique. Data were collected by using questionnaire adapted from the instrument of Pop (2016). A Cronbach co-efficient alpha of 0.821 was obtained indicating that the instrument was reliable. Mean and standard deviation were used in analysing the data. The study revealed that the respondents did not see themselves as having the perfect body shape, were not satisfied body shape and size and were not satisfied with their weight. Overall, the respondents had poor body image. The study revealed also that media and peer influences were the main factors which influenced body image perception among the students. The other identified factors were society and cultural background, family members and partners. It was recommended that university authorities should organise outreach programmes for students on how to improve their self-esteem and self-image so that the incidence of poor body image can be reduced.